Campus rape culture : identity and myths - Huck, Jennifer L. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"The book looks at rape myths and rape culture within the university environment, examining the development of social identities in the creation and support of such culture. Building on a four-year research project, this book demonstrates how an understanding of rape culture and of the falsity of rape myths amongst students and staff at university is often at odds with an understanding of the degree to which sexual assaults take place, and of why they take place. This book explores how traditionally held beliefs of sex roles between men and women, poor conceptions of consent processes, lack of available data, and an inability to see the full continuum of sexual assault limits the knowledge of sexual assaults inside the university community. Taken together the studies demonstrate how socialized social identities of masculinity and femininity hold power in how consent, sexual assaults, and sexual behaviors manifest through cultural values of rape myths and hook-ups. Universities are challenged to examine their sexual assault programming in connection to Title IX and beyond to create educational opportunities about rape culture and rape myths suitable for their students, faculty, and staff. Written in a clear and direct style, this is essential reading for all those engaged in research about rape culture, sexual assault, and violence against women"--
OCLC-licensed vendor bibliographic record.
Keywords: Rape in universities and colleges; Sex differences in education; Group identity; Universities and colleges -- Social aspects; Sexual harassment in universities and colleges; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Gender Studies; SOCIAL SCIENCE / Violence in Society